(untitled) (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
In the frame of this investigation, the homogeneity of six (6) ingots of aluminum alloy EN AW-5083 cast by semi-continuous vertical Direct Chill casting (DC) Process was investigated by tensile mechanical properties determination. The investigation followed the static design of the Latin square. Determination of the ultimate tensile strength and elongation across the cross-sectioned sliced at the ingots’ fronts and rears in as-cast state revealed differences per cross section of each particular slice. Comparison of obtained differences enabled evaluation of tensile mechanical properties homogeneity of the ingots as a whole. The influence and significance of homogenization was also quantified by comparing the obtained measurement results for as-cast and homogenized state. The results were processed using the StatSoft® STATISTICA 13.2 software package.